Comparison of the caries-protective effect of fluoride varnish with treatment as usual in nursery school attendees receiving preventive oral health support through the Childsmile oral health improvement programme — the Protecting Teeth@3 Study: a randomised controlled trial. Issue 1 (December 2015) - Wright, William; Turner, Stephen; Anopa, Yulia; McIntosh, Emma; Wu, Olivia; Conway, David; Macpherson, Lorna; McMahon, Alex
Abstract Background The Scottish Government set out its policy on addressing the poor oral health of Scottish children in 2005. This led to the establishment of Childsmile, a national programme designed to improve the oral health of children in Scotland. One element of the programme promotes daily tooth brushing in all nurseries in Scotland (Childsmile Core). A second targeted component (Childsmile Nursery) offers twice-yearly application of fluoride varnish to children attending nurseries in deprived areas. Studies suggest that fluoride varnish application can reduce caries in both adult and child populations. This trial aims to explore the effectiveness and cost-effectiveness of additional preventive value fluoride varnish application compared to Childsmile Core. Methods/Design The Protecting Teeth@3 Study is an ongoing 2 year parallel group randomised treatment as usual controlled trial. Three-year-old children attending the ante pre-school year are randomised (1:1) to the intervention arm (fluoride varnish & treatment as usual) or the control arm (treatment as usual). Children in the intervention arm will have Duraphat® fluoride varnish painted on the primary tooth surfaces and will continue to receive treatment as usual: the core Childsmile Nursery intervention. Children in the treatment as usual arm will receive the same series of contacts, without the application of varnish and will also continue with the Childsmile Core intervention. Interventions are undertaken by Childsmile trained extended duty dental nurses at six-monthly intervals. Participants receive a baseline dental inspection in nursery and an endpoint inspection in Primary 1 at the age of 5 years old. We will use primary and secondary outcome measures to compare the effectiveness of Duraphat® fluoride varnish plus treatment as usual with treatment as usual only in preventing any further dental decay. We will also undertake a full economic evaluation of the trial. Trial registration This study is registered at ClinicalTrials.gov. Number:NCT01674933 (24 August 2012).